Path dependence and institutional breakthrough: The transformation of children’s education welfare policy in China - Chen, Hongyu (Education Insights, 2026)
Since the founding of the People’s Republic of China, the national children’s education welfare policy has undergone three major historical stages: early exploratory development under the traditional planned economy, comprehensive institutional adjustment driven by the transition to a socialist market economy, and integrated innovation tailored to the requirements of the new era. The profound transformation of China’s children’s education welfare policy has been fundamentally driven by a threefold structural logic. This framework consists of ongoing political system reform, the rapidly advancing level of macroeconomic development, and the gradual transformation of underlying cultural values regarding child-rearing and education. At the same time, viewed through the theoretical lens of historical institutionalism, this policy evolution has exhibited a distinct pattern of path dependence. Under the persistent influence of complex factors such as institutional cost effects, organizational learning effects, systemic coordination effects, and societal adaptive expectations, this path dependence has frequently hindered rapid policy change and structural breakthroughs. At present, despite significant progress, major systemic challenges remain deeply entrenched. These include the unequal regional distribution of high-quality educational resources, excessive academic pressure placed on students, and the broader demographic context of persistently low fertility rates. Looking ahead, to overcome these institutional bottlenecks, it is absolutely necessary to strengthen comprehensive legal safeguards, optimize the equitable allocation of public resources, and build a diversified collaborative governance mechanism. Ultimately, these strategic interventions are essential in order to successfully promote the sustainable, high-quality development of children’s education welfare across the nation.